ADULT LEARNING AS MIGRANTS’ INTEGRATION TOOL: NORWEGIAN EXPERIENCE - Babushko, Svitlana R.; Solovei, Liudmyla S. (Educological discourse, 2017)
The article deals with the adult migrants’ learning challenges. Until recently the problem has been seen as the simple second language acquisition by migrants. The practice showed its inconsistency due to the wide range of skills and competences which adult migrants had to acquire in a new community. European Council has worked out the common policy of integration of migrants, one of the powerful tools being learning. Despite the common integration policy, every European country has some unique features of their migrants’ policy. The authors of the article analyze the Norwegian experience in this field and some legislative documents that provide its efficiency. The scientific research methods of analysis, synthesis, comparison and generalization have been used to describe the achievements of Norway. Hence to the systematic and structural method the Norwegian peculiarities of migrants’ learning policy have been identified. It has been found out that like other European Union member-countries Norway has the same tendency in migrant’s educational policy. There is a shift from simple language learning of the host country to meeting other educational needs of migrants. Yet, the peculiar feature in Norway is the model of integrating migrants into the society with the help of learning. There have been identified three constituent elements: learning the Norwegian language, learning social studies, literacy learning. Being characterized in short they have given the grounds to the conclusion that only in their unity, they provide the effectiveness of the Norwegian migrants’ learning model and meet the current demands of the society and migrants themselves.